Efecto del aprendizaje colaborativo en el desarrollo del pensamiento creativo en la enseñanza de las ciencias naturales (2019)
This investigation was based on determining the teamwork learning effect in the creative thinking development during the science teaching among third grade students of the Malvina cultural I.E.D. from the city of Barranquilla. Substantiated under Torrance theory (1962) regarding the creativity evaluation model, that defines creativity as the process in which hypothesis are set in order that they can developed ideas that can be tested Transformed and report the results obtained to fill any existing information problems according to Guilford (1950). This emerges the study to establish a team work learning strategy to modify. The thinking habits and keep them always changing framed in an analytical empirical paradigm with a quasiexperimental design and developed with a 97 student’s population using a test and inventory program as tools to improve the fluency and originality as creative thinking components. As a result and conclusion we obtained that there is a positive effect using the team work learning strategy in the creative thinking development